Immune Infiltration Pattern Associated with Diagnosis and Development in benign Prostatic Hyperplasia - Xu, Xianglai; Wang, Ying; Sihong, Zhang; Lu, Jidong; Zheng, Xiaoyu; Wang, Jiajun; Zhu, Yanjun; Guo, Jianming (Urology Journal, 2021)
Purpose: Benign prostatic hyperplasia (BPH) significantly reduces the quality of life. However, the biological mechanisms of BPH development remain largely unknown. We aimed to investigate the essential genomic and immunogenic features in BPH. Materials and Methods: Transcriptome profiling and clinical data of BPH and normal prostate samples were acquired from GEO datasets. The discovery sets were composed of GSE119195, GSE7307, GSE101486, while validation set was GSE132714. ESTIMATE and CIBERSORT was used to investigate the immunogenic features. Furthermore, transcriptional and weighted gene co-expression network analysis (WGCNA) was used for further analysis. Results: BPH samples presented higher immune score. Meanwhile, CIBERSORT deconvolution revealed that BPH exists significantly abundant M2 Macrophages, follicular T helper cells, resting mast cells, and fewer plasma cells, activated CD4+ memory T cells and activated mast cells. WGCNA analysis also revealed significantly enriched immune-related modules in BPH. Transcriptomic analysis identified SOCS3, IL6, C3, IGF1, NOTCH1 and VCAN as key regulators of immunogenic phenotype in BPH. Moreover, we generated an immunological gene signature for BPH, which worked well in validation cohort. Conclusion: In our study, BPH samples exhibited a distinct immune infiltration pattern, represented by an immunological gene signature. This genomic-based assessment model reveals the potential transcriptomic patterns during BPH development.